Five-Year Survival in Patients with 3-Vessels Coronary ArteryDisease and Diabetes Mellitus Undergoing Coronary ArteryBypass Graft, Coronary Percutaneus Intervention, or ReceivingPharmacological Therapy in Cipto Mangunkusumo Hospital - Setiawan, Andreas Arie; Panggabean, Marulam; Yamin, M; Setiati, Siti (Jurnal Penyakit Dalam Indonesia, 2016)
Introduction. Revascularization results in patients with diabetes mellitus (DM) and coronary artery disease involving 3 vessels (CAD 3VD) undergo coronary artery bypass surgery (CABG) are better compared with those undergo percutaneous coronary intervention (PCI) or medical therapy. However, CABG is not always done despite being recommended in accordance with Syntax Score because some patients unwilling to undergo CABG or PCI . This trial determined whether the choice of revascularization affect 5-years survival. Methods. This was a retrospective cohort study with survival analysis to examine the 5-years survival rate of CAD 3VD DM patients undergoing CABG, PCI, or medical therapy. The study was conducted using secondary data of 126 CAD 3VD DM patients who underwent CABG, PCI, or medical therapy at Cipto Mangunkusumo Hospital in 2006-2007 and followed up to 2011-2012 if there any incident died. Results. Best survival was seen in the CABG group (93.5%). The largest proportion of death occured in the medical therapy group (36.1%). The CABG survival was significantly better than the IKP (p=0.01) and medical therapy (p=0.001). PCI group had better survival than medical therapy (69.5% vs. 63.9%). Although not statistically significant, but the proportion of complaints after revascularization in PCI group were found less than medical therapy group (52% vs. 38%). Syntax score that assesses the complexity of stenosis had a significant association with survival (p 0.039). Conclusions.5-years survival of CAD 3VD DM patients is best obtained in the group that underwent CABG. 5-year survival of CAD 3VD DM patients who underwent PCI better than medical therapy but was not statistically significant. Factor that affect the 5-years survival is the complexity stenosis viewed by the Syntax score.